Development of P-on-N silicon photomultiplier prototype for blue light detection. (6th November 2017) - Lim, K.T.; Lee, D.; Park, K.; Kim, G.; Lee, M.; Kim, Y.; Kim, M.; Kim, J.; Kim, H.; Lee, E.; Sul, W.S.; Cho, G.
Abstract: In this paper, we report a preliminary study on the electrical and optical properties of the first P-on-N SiPM prototype developed at KAIST with a collaboration of NNFC. The sensors were fabricated on a 200 mm n-type silicon epitaxial-layer wafer via customized CMOS process at NNFC. Measurements on the reverse current were carried out on a wafer-level with an auto-probing station and breakdown voltage was found as 32.3 V. As for optical characterization, gain, dark count rate, and photon detection efficiency have been measured as a function of bias voltage at room temperature. In particular, we show that the device had a comparable gain of ∼ 10 6 with respect to conventional PMTs and had a peak sensitivity in blue light regime. Furthermore, we attempt to explain possible causes of some of phenomena seen from the device characterization.